The location of subregional offices: an emerging issue for HR managers in government. - Fok LY; Hartman SJ; Fok WM (Public Personnel Management)
As the 21st century approaches, HR managers are increasingly finding it necessary to 'think outside the box' to find ways to deliver governmental services to users of those services who may be scattered widely throughout a region or ter ritory. Specifically, the HR function finds itself faced with seemingly contradictory pressures: obtaining personnel to deliver top-quality service in an era of cynicism, when users are often skeptical of the ability of government to 'come through' for t hem, and controlling costs and personnel budgets amid calls for reducing the size of government. In this paper, we propose that much progress toward dealing with these questions can be made, if HR managers begin by asking where the people deliveri ng the services should be located. All too often, this approach has not been taken, and managers have simply assumed that cost savings are best effected by centralization, or that service is best provided in decentralized locations. We suggest that there may be no one best answer and provide methodology for use by HR managers in guiding their analysis. In this paper, three techniques that are understandable and practical for use by nonquantitatively oriented managers are used to analyze the situation co nfronting a large government agency. The techniques used are the traditional center-of-gravity method, the Ardalan's heuristic, and a proposed simulation routine. We compare results when these approaches are applied when the agency considers the establis hment of one or more subregional offices. Results from the Ardalan heuristic and the proposed simulation routine are extremely close to each other. When applied to our case situation, we found that one additional office reduces total distance traveled by 25 percent and two additional offices reduce total distance traveled by close to 50 percent, a result with a potential for substantial savings to that agency.